Administration of the Estate under Regulation (EU) No. 650/2012 - Górecki, Jacek (Review of European and Comparative Law, 2021)
In the period between the deceased person’s death and division of assets in the deceased person’s estate among the heirs, an essential matter is administration of the estate. Persons exercising such administration should have adequate competences allowing them to perform factual and legal acts in relation to assets in the succession estate. The range of such persons and the scope of their competences differ in specific Member States of the EU. The law applicable to the administration of the estate, as well as other matters relating to succession, is currently designated by the Regulation (EU) No. 650/2012. This article is devoted to an analysis of the provisions of that Regulation on the administration of the estate. In addition, the article discusses the issue of qualifying the institution of succession administration as applicable in Poland with regard to an enterprise belonging to the succession estate. As a result of the investigations made, it can be concluded that administration of the estate is governed by the law applicable to the entirety of succession matters (lex successionis). This is the case also in respect of the succession administration recently introduced in Poland. Grounds for a different treatment of the succession administration cannot be found in Art. 30 of Regulation (EU) No. 650/2012.